2021
DOI: 10.21608/jfds.2021.92242.1026
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aflatoxin M1 Contamination in Egyptian Milk and Cheese تقييم تلوث اللبن والجبن في السوق المصري بالأفلاتوکسين M1

Abstract: A screening survey of the presence of aflatoxin M1 (AFM1) was carried out on 170 samples of Egyptian dairy products. Selected samples included raw buffalo or cow milk, pasteurized milk, UHT milk, fermented milk, soft cheese, hard cheese, and processed cheese were analyzed by competitive ELISA technique. Out of 60 liquid milk and fermented milk samples analyzed, 12 samples (20%) were found to be contaminated with AFM1, at levels ranging from 10.12 to 86.54 ng/kg. Eight from the positive samples (66.6%) failed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…The percentage of contaminated milk samples by AFM1 was (80%) which is considered greater than that illustrated by Amer and Ibrahim (2010) (38%); Ismaiel et al (2020) (21.6% first year and 18.3% the second year), El-Hofi and Abo El-Naga (2021) (20%) and lower than that reported by Shaker and Elsharkawy (2014) (100%) ( Amer and Ibrahim, 2010 ; Shaker and Elsharkawy, 2014 ; Ismaiel et al , 2020 ; El-Hofi and Abo El-Naga, 2021 ). Our results showed that only 7% of examined milk samples contaminated by Aflatoxins M1 were higher than the EC limit, which was lower than those reported by Ismaiel et al (2020) .…”
Section: Discussionmentioning
confidence: 58%
“…The percentage of contaminated milk samples by AFM1 was (80%) which is considered greater than that illustrated by Amer and Ibrahim (2010) (38%); Ismaiel et al (2020) (21.6% first year and 18.3% the second year), El-Hofi and Abo El-Naga (2021) (20%) and lower than that reported by Shaker and Elsharkawy (2014) (100%) ( Amer and Ibrahim, 2010 ; Shaker and Elsharkawy, 2014 ; Ismaiel et al , 2020 ; El-Hofi and Abo El-Naga, 2021 ). Our results showed that only 7% of examined milk samples contaminated by Aflatoxins M1 were higher than the EC limit, which was lower than those reported by Ismaiel et al (2020) .…”
Section: Discussionmentioning
confidence: 58%